MANAJEMEN RISIKO KERUGIAN ANGKUTAN UMUM PENUMPANG PERUM DAMRI KABUPATEN KEPULAUAN SELAYAR - Irawati, Irawati; Mannaga, Idham (Patria Artha Journal of Accounting dan Financial Reporting, 2023)
Risk management is a process for measuring or assessing risk, and developing strategies for managing that risk. This study aims to determine how risk management is implemented by Perum DAMRI Makassar Branch. This research is a type of field research (field research). Data collection methods in this study were carried out through interviews and documentation. The analysis technique used is through the process of data collection, data reduction, data presentation, and drawing conclusions. These results indicate that risk management in the Makassar branch of Perum DAMRI, especially in the Selayar Islands Regency, is moving towards a better direction. And the method used by Perum DAMRI Makassar Branch is the same as the risk management process. And there are 3 main processes in risk management for public transport passanger losses at Perum DAMRI, Selayar Archipelago Regency, 1.) namely risk identification, namely the causes and sources of risk of loss due to the lack of publicinterest in using DAMRI services and because the tariff is low below the operational value, 2.) risk evaluation, ifthe DAMRI buses in the Selayar Archipelago Regency continue to lose money and there is no increase, the buses will be withdrawn and look for routes thathave the potential for profit, and 3.) risk management, namely the risk assumption.